Long Period Grating Based Fibre Optic Chemical Sensors - Korposh, Sergiy; Lee, Seung-Woo; James, Stephen W. (Springer, 2016)
The principle of operation of optical fibre long period grating (LPG) sensors is described. In particular, the chapter explores the use of LPGs as a chemical sensing platform, discussing the fabrication of LPGs and the various approaches that have been employed to modify the cladding of the LPG and thus sensitise the LPG. Examples of the practical application of LPG chemical sensors are provided.